The Influence of Leadership Behavior, Work Skills and Achievement Motivation on Work Productivity Moderated by Work Discipline Case Study at PT. Audy Jasatrans Logistics - Iin Indrawati (Dinasti International Journal of Management Science, 2023)
Work productivity in a logistics company is the company's effort in handling various requests from consumers with the goal that goods or services can be carried out or distributed quickly to the destination according to demand. This study aims to propose the effect of leadership behavior, work skills and achievement motivation on work productivity moderated by work discipline. The method used in this study is a quantitative method using a causal study survey approach. This research was conducted at PT.Audy Jasatrans Logistik with a total sample of 150 people, namely all employees working at PT. Audy Jasatrans Logistics. The data analysis technique in this study used the Structural Equation Modeling – Partial Least Square (SEM-PLS) method with the help of the SMART PLS application to carry out research data analysis. In this study, instrument testing was carried out by conducting validity tests, reliability tests, outer models and inner models. The results of this study indicate that leadership behavior has no effect on work productivity, work skills have an effect on work productivity, achievement motivation has an effect on work productivity, work discipline has no effect on work productivity, work discipline moderation can strengthen the influence of leadership behavior on work productivity, discipline moderation work can strengthen the effect of work skills on work productivity and moderation of work discipline can weaken the effect of achievement motivation on work productivity.